TINGKAT KEPUASAN PASIEN TERHADAP KONDISI RUANG DAN WAKTU TUNGGU RESEP DI RS X KARANGASEM - Oviani, Gusti Ayu; Indraswari, Putu Ika Indah; Ristayani, Ni Komang; Yunita, Ella (Institut Teknologi dan Kesehatan Bintang Persada, 2024)
The importance of waiting room conditions and prescription waiting time is one of the factors for patient satisfaction. Patient satisfaction is a level of patient feeling that arises as a result of the performance of health services obtained after the patient compares it with what he or she expects. The purpose of this study was to determine the average waiting time for non-prepared prescriptions, to determine the level of patient satisfaction with the condition of the room and the waiting time for prescriptions at X Karangasem Hospital. This type of research is descriptive research, where the sample was taken by purposive sampling. The results of this study are the average waiting time for non-prepared prescriptions at the X Karangasem Hospital Polyclinic is 22.44 minutes per prescription, where the average waiting time for prescription services does not meet the standards set by IFRS X Karangasem, which is ? 15 minutes. The results of the level of patient satisfaction with the condition of the waiting room are 71.30% and the level of patient satisfaction with the waiting time for prescriptions is 70.76%, so the average level of patient satisfaction is stated as satisfied with a percentage of 71.03%.